Abdominal fat indicators: anthropometry vs dual energy x-ray absortometry - Marina Kanthack Paccini; Gisela Arsa; Maria Fátima Glaner (Revista Brasileira de Cineantropometria e Desempenho Humano, 2008)
http://dx.doi.org/10.5007/1980-0037.2008v10n3p283